Stages of Formation and Development of Public Education in Podillia (1864–1917) - Bourdouvalis, Kateryna (Pedagogical Discourse, 2023)
The purpose of the article is to reveal the stages of formation and development of public education in Podillia in 1864–1917. To achieve this goal, the following research methods were used: analysis of historical and pedagogical scientific publications and dissertations, which helped to clarify the stages of formation of public education; systematization, generalization, synthesis of information, interpretation and clarification of concepts, comparison. The purpose of the article is to characterize the peculiarities of the periods of the outlined problem, to highlight the pedagogical thought of scholars of this problem, to reveal the stages of development of the periodization of public education. It is found that various aspects of the history of the development of public education are analyzed in the works of teachers and historians: N. Hupan, L. Drovoziuk, M. Vorolis, O. Kosholap, O. Udoda. The author’s periodization of public education in Podillia in 1864–1917 is developed and presented. It is established that the period under study is divided into three periods: the first period covers 1864–1870, the second period – 1870–1902, the third period – 1903–1917. It was found that in the first period, the imperial authorities adopted the «Regulations on Primary Public Schools». It officially declared the availability of education for the masses. The author examines the formation of the legislative framework and the subordination of schools to various departments. In the second stage, it is considered that the authorities are returning to the religious component of schools and relying on church-parish schools. It is traced that during the period under study, the program of educational institutions of public education was formed. It has been established that theological disciplines and the Russian language, arithmetic, history, geography, natural history, the basics of planimetry, drawing, and church singing were taught in parochial schools. It is emphasized that in the third period, zemstvos authorized by the imperial authorities joined the development of educational institutions. They were responsible for opening educational institutions and financing them.